Islam di Pesisir Utara Jawa dalam Simbol Sufistik Naskah Sejatine Manusa - Purnomo, Bagus; Dinar, Afifah (Jurnal Lektur Keagamaan, 2023)
ABSTRACT This study explores the integration process of Islam in the northern coast of Java Island, where the entrance of Islam occurred gradually. There was an assimilation process that can be demonstrated by physical evidence, one of which was the Sejatiné Manusa (SM) manuscript. The Sufistic symbols in the Sejatiné Manusa (SM) manuscript were analyzed using a qualitative method with a socio-intellectual historical approach. The study resulted in text-based strengthening of Islamic identity on the Java coast, as written manuscripts have high historical objectivity and authenticity in capturing historical dynamics. This study also demonstrates that, contrary to Geertz et al.'s conception, Islam on the coast is not Islam mixed with Hindu-Buddhist teachings and local religions, but rather the kind of Islam which adopts local elements that are not contradictory to Islam and reinforces its teachings through a continuous process of dyna-mic transformation. Furthermore, this indicates that Islam is not extreme. Keywords: Islam, the Coast, Java, Symbol, Sufis, Sejatiné Manusa   ABSTRAK Tulisan ini mendiskusikan proses asimilasi Islam di pesisir utara Pulau Jawa, di mana proses kedatangan Islam tidak semata-mata datang secara tiba-tiba, namun terdapat proses asimilasi yang dapat dibuktikan dengan bukti fisik, yakni dalam naskah Sejatiné Manusa (SM). Penelitian ini menggunakan metode kualitatif dengan pendekatan sejarah sosial-intelektual, di mana akan fokus menganalisis simbol-simbol sufistik yang terdapat di dalam naskah Sejatiné Manusa (SM). Peneguhan identitas Islam di pesisir berbasis naskah menjadi hasil penelitian dalam artikel ini, karena naskah memiliki objektivitas dan otentisitas kesejarahan yang tinggi dalam merekam dinamika yang terjadi di masa lampau. Naskah ini juga membuktikan bahwa Islam di pesisir bukanlah Islam singkretik yang bercampur dengan ajaran Hindu-Budha dan agama lokal, seperti konsepsi Geertz dkk, tetapi Islam yang bercorak khas; yang mengadopsi unsur-unsur lokal yang tidak bertentangan dengan Islam dan menguatkan ajarannya melalui proses transformasi dinamis secara terus-menerus.Selain itu, juga meneguhkan bahwa Islam bukanlah agama yang ekstrem. Kata Kunci: Islam, Pesisir, Jawa, Simbol, Sufisme, Sejatiné Manusa